A short history of world war i eaudiobook - Stokesbury, James L. (Recorded Books Inc., 1991)
James Stokesbury's keen, perceptive vision and subtle sense of humor make this fast-paced chronicle of the First World War an excellent introduction to the conflict for students and a great refresher course for armchair historians. A Short History of World War I is a riveting account of the famous wartime engagements, the legendary leaders, and the behind-the-scenes events that drew countries across the globe into devastating conflict.